Limited Progress in the Treatment of HCC - Rizzo, Toni (MD Conference Express, 2014)
The main risk factors for hepatocellular carcinoma (HCC) are hepatitis C virus, hepatitis B virus, and alcohol consumption, which can lead to cirrhosis, genomic instability, and progression to HCC. This process involves a cycle of regeneration and necrosis that induces release of cytokines, proangiogenic factors, and profibrotic factors. Fibrosis and increased cell proliferation can result in formation of a dysplastic nodule, marked genomic instability, loss of p53, and development of HCC [Farazi PA, DePinho RA. Nat Rev Cancer. 2006].